2019
DOI: 10.3389/fnins.2019.00385
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Electrode Size for Multi-Scale Extracellular-Potential Recording From Neuronal Assemblies

Abstract: Advances in microfabrication technology have enabled the production of devices containing arrays of thousands of closely spaced recording electrodes, which afford subcellular resolution of electrical signals in neurons and neuronal networks. Rationalizing the electrode size and configuration in such arrays demands consideration of application-specific requirements and inherent features of the electrodes. Tradeoffs among size, spatial density, sensitivity, noise, attenuation, and other factors are inevitable. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 85 publications
(151 reference statements)
2
116
0
Order By: Relevance
“…A common assumption is that large electrodes (> 50 μm in diameter) are adequate for recording compound field potentials from a wide neuronal ensemble, while small electrodes (< 20 μm) are more suitable for recording extracellular action potentials generated by few nearby neurons (Rossant et al, 2016). Using arrays containing platinum electrodes of different sizes, it was found that noise and signal attenuation depend more on the electrode impedance than on electrode size; by reducing the impedance of small electrodes by surface modifications, the SNR of axonal action potentials was increased (Viswam et al, 2019). For this reason current micro-electrodes design presents macroporous structures in order to maximize surface for signal acquisition.…”
Section: Electrode Configurationmentioning
confidence: 99%
“…A common assumption is that large electrodes (> 50 μm in diameter) are adequate for recording compound field potentials from a wide neuronal ensemble, while small electrodes (< 20 μm) are more suitable for recording extracellular action potentials generated by few nearby neurons (Rossant et al, 2016). Using arrays containing platinum electrodes of different sizes, it was found that noise and signal attenuation depend more on the electrode impedance than on electrode size; by reducing the impedance of small electrodes by surface modifications, the SNR of axonal action potentials was increased (Viswam et al, 2019). For this reason current micro-electrodes design presents macroporous structures in order to maximize surface for signal acquisition.…”
Section: Electrode Configurationmentioning
confidence: 99%
“…Wellestablished semiconductor industry manufacturing capabilities allow recording electrodes to be reduced in size and integrated with high density using complementary metaloxide-semiconductor (CMOS) technology. However, implementing extremely small metal electrodes poses an enormous challenge due to parallel interfacing requirements imposed by relatively sizable peripheral recording electronics that secure the connections between multiplexed inputs and outputs [261,267,268]. Due to this fundamental bottleneck, multiplexed measurement capabilities of MEAs have been limited [267].…”
Section: Electro-plasmonic Nanoantenna and Electrophysiologymentioning
confidence: 99%
“…The influence of size, impedance and material of recording sites on neural recordings is relatively well studied [30][31][32][33]. However, prior research investigating the optimal placement of recording sites on silicon shanks to achieve high quality recordings is scarce and contradictory [34][35][36].…”
Section: Introductionmentioning
confidence: 99%